Reflecting Forewords - Chambers, Robert; Lewin, Tessa (Practical Action Publishing, 2024)
Reflecting Forewords is an unashamedly ambitious book. Full of lessons from the past that are relevant for the future, it is a compilation o f inspiring forewords from books written by Robert Chambers; one of th e most influential and prolific scholars to write about participation, poverty, and knowledge in development studies. Tessa Lewin, Robert’s colleague and an experienced practitioner and researcher, has worked w ith Robert to weave together the forewords alongside a series of refle ctions from other practitioners and scholars in the field. In our worl d of dramatic unforeseeable change, Reflecting Forewords seeks to draw lessons and present insights that should not be ephemeral, but can co ntribute on a lasting way to policy, practice and research in the rest of our 21st century. Readers will draw their own conclusions. The ori entation is forward-looking into our unpredictable future, stressing t he need to be alert, in touch, nimble, and guided by reflexivity. This curated collection of resurfaced gems will inspire development profes sionals, teachers and graduate students of development studies, policy makers, historians of development thinking and practice, activists, an d all those who are concerned with a better life for all.